Analisis Kemampuan Keuangan Daerah dalam Pelaksanaan Otonomi Daerah Tahun 2007-2011 di Kota Makassar - Ermita Savitry; Hasrat Arief Saleh; Indar Arifin (Departemen Ilmu Pemerintahan Fisip Unhas, 2011)
Abstract: This writing to determine the level of development of the financial capacity of Makassar in order to support the implementation of regional autonomy and Local Revenue Contribution to the Budget Revenue and Expenditure Makassar fiscal year 2007-2011. The results of the study, the ratio of the regional of financial independence obtained an average yield of 18.30% on the pattern of relationships are instructive. The ratio of the degree of fiscal decentralization and routine capability index ratio shows the ability of local finance is less, amounting to 15.39% and 24.99%. In harmony ratio, routine expenditure is greater than the gap of development expenditure amounted to 25.60%. The ratio of growth, overall experience negative growth, due to an increase in local revenue and total revenue not followed by construction spending growth, but it is followed by the growth of expenditures. Local Revenue Contribution to the Budget Revenue and Expenditure, still less, amounting to 15,39%. By looking at the results of the analysis, development of the financial ability of the city of Makassar in the implementation of regional autonomy were deemed to be lacking.Keywords: Regional autonomy, financial, Makassar CityAbstrak: Tulisan ini bertujuan untuk mengetahui tingkat perkembangan kemampuan keuangan Kota Makassar dalam rangka mendukung pelaksanaan otonomi daerah dan konstribusi Pendapatan Asli Daerah terhadap Anggaran Pendapatan dan Belanja Daerah Kota Makassar tahun anggaran 2007-2011. Hasil penelitian, rasio kemandirian keuangan daerah yang memperoleh hasil rata-rata sebesar 18,30% atau berada pada pola hubungan instruktif. Rasio derajat desentralisasi fiskal dan rasio indeks kemampuan rutin yang menunjukkan kemampuan keuangan daerah masih kurang, yaitu sebesar 15,39% dan 24,99%. Pada rasio keserasian, pengeluaran belanja rutin lebih besar dibandingkan dengan belanja pembangunan dengan gap sebesar 25,60%. Rasio pertumbuhan, secara keseluruhan mengalami pertumbuhan yang negatif, karena peningkatan pendapata asli daerah dan total pendapatan daerah tdak diikuti oleh pertumbuhan belanja pembangunan, tetapi diikuti oleh pertumbuhan belanja rutin. Konstribusi PAD terhadap APBD, masih kurang, yaitu sebesar 15,39%. Dengan melihat hasil analisis tersebut, perkembangan kemampuan keuangan Kota Makassar dalam rangka pelaksanaan otonomi daerah dianggap masih kurang.Kata kunci: Otonomi Daerah, Keuangan, kota Makassar